2021
DOI: 10.7554/elife.65311
|View full text |Cite
|
Sign up to set email alerts
|

PMCA-generated prions from the olfactory mucosa of patients with Fatal Familial Insomnia cause prion disease in mice

Abstract: Background: Fatal Familial Insomnia (FFI) is a genetic prion disease caused by the D178N mutation in the prion protein gene (PRNP) in coupling phase with methionine at PRNP 129. In 2017, we have shown that the olfactory mucosa (OM) collected from FFI patients contained traces of PrPSc detectable by Protein Misfolding Cyclic Amplification (PMCA).Methods In this work, we have challenged PMCA generated products obtained from OM and brain homogenate of FFI patients in BvPrP-Tg407 transgenic mice expressing the ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Regarding the potential for the human NC to shed infectious prions, studies using transgenic mice have shown that OM pellets collected from sporadic CJD is infectious, but the amount of infectivity in the OM brushings was more than 10,000-fold less infectious per unit volume than that for infected brain tissue from these same patients. These findings were similar to the results of a transmission study demonstrating that PMCA-generated products from OM obtained from FFI patients inoculated into transgenic mice expressing the bank vole prion protein were infectious [89]. To date, there has been just one study of human nasal secretions (collected from the nasal vestibule), which found prion infectivity in two of 13 samples, indicating that there was lower, and in most cases undetectable, seeding activity in the nasal secretions compared to the OM nasal brushings [90].…”
Section: Evidence From Human Prion Diseasessupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the potential for the human NC to shed infectious prions, studies using transgenic mice have shown that OM pellets collected from sporadic CJD is infectious, but the amount of infectivity in the OM brushings was more than 10,000-fold less infectious per unit volume than that for infected brain tissue from these same patients. These findings were similar to the results of a transmission study demonstrating that PMCA-generated products from OM obtained from FFI patients inoculated into transgenic mice expressing the bank vole prion protein were infectious [89]. To date, there has been just one study of human nasal secretions (collected from the nasal vestibule), which found prion infectivity in two of 13 samples, indicating that there was lower, and in most cases undetectable, seeding activity in the nasal secretions compared to the OM nasal brushings [90].…”
Section: Evidence From Human Prion Diseasessupporting
confidence: 88%
“…To date, there has been just one study of human nasal secretions (collected from the nasal vestibule), which found prion infectivity in two of 13 samples, indicating that there was lower, and in most cases undetectable, seeding activity in the nasal secretions compared to the OM nasal brushings [90]. Therefore, while the data suggest that the potential for the spread of prion diseases between humans is limited, precautions during surgical procedures involving the nasal cavity are warranted [89,90].…”
Section: Evidence From Human Prion Diseasesmentioning
confidence: 99%
“…Generally, PMCA products possess both biochemical characteristics and infectivity of prions, whereas RT-QuIC products are more of a ref lection of prion fibrillation [19][20][21], which usually lack infectivity [22]. Overcoming natural species barriers of prion infection is observed in the experimental bioassays of PMCA product inoculation.…”
Section: Hamster-and Mouse-adapted Scrapie Agents Failed To Induce Co...mentioning
confidence: 99%
“…The transmissible nature of prions means that they can self-propagate or seed the conversion of normal PrP into prions. This seeding ability allows the disease to spread through the brain and can be measured by highly sensitive and specific assays such as Real-time Quaking-Induced Conversion (RT-QuIC) and Protein Misfolding Cyclic Amplification (PMCA) [7][8][9]. The D178N mutation does not result in steady-state production of prions in cell culture models; however, it directly alters the biochemical properties of PrP, producing heavily glycosylated PrP [4][5][6].…”
Section: Introductionmentioning
confidence: 99%